2013
DOI: 10.7314/apjcp.2013.14.9.4965
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Cancer: a Systematic Literature Review

Abstract: This study aimed to discuss the consumption of alcohol as a risk factor for major cancers. We performed a search in the PubMed database, using the following inclusion criteria: meta-analysis published in English in the last 10 years that addressed the relationship between alcohol and the risk of developing cancer. The results indicate that moderate to heavy consumption of alcohol increases the risk of developing cancer of the oral cavity and pharynx, esophagus, stomach, larynx, colorectum, central nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 33 publications
1
49
1
7
Order By: Relevance
“…As of 2004, there was an increase in the number of individual studies and systematic reviews with meta-analysis, and they left little doubt about the association between breast cancer and the use of tobacco and/or alcohol. Alcohol consumption above all was clearly associated with this malady (de Menezes et al, 2013;Gao et al, 2013;Gou et al, 2013).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As of 2004, there was an increase in the number of individual studies and systematic reviews with meta-analysis, and they left little doubt about the association between breast cancer and the use of tobacco and/or alcohol. Alcohol consumption above all was clearly associated with this malady (de Menezes et al, 2013;Gao et al, 2013;Gou et al, 2013).…”
Section: Introductionmentioning
confidence: 85%
“…However, since the end of the 1980's, a multitude of articles have been published about the fact that the regular 1 consumption of alcohol and use of tobacco represent risk factors for breast cancer (Stefani et al, 2011;CardenasRodriguez et al, 2012;de Menezes et al, 2013;Gao et al, 2013;Gou et al, 2013). Interestingly, some of the first studies actually showed a reduction of the risk of breast cancer with tobacco use (Meara et al, 1989) or alcohol consumption (Adami et al, 1988;Liu, M. et al, 2014b), or no association between smoking and breast cancer (Smith et al, 1994), further more, did not find any association between alcohol consumption and an increased risk of cancers of the lung, bladder, endometrium and ovary (de Menezes et al, 2013), and it was also observed that alcohol consumption may be inversely related to thyroid cancer. And on the other hand, in certain study suggest that cigarette smoking is associated with an elevated risk of breast cancer among former smokers in Serbia (Ilic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ladeiras-Lopes and colleagues' review of 42 cohort studies showed relative risk (RR) of GC were 1.62 in male smokers (95% confidence intervals (CI): 1.50-1.75) and 1.20 in female smokers (95%CI: 1.01-1.43) compared with those who had never smoked (Ladeiras-Lopes et al, 2008). With regard to alcohol drinking, some researchers believe that it is an important risk factor for numerous cancers worldwide, including cancer of the oral cavity and pharynx, esophagus, stomach, larynx, colorectum, central nervous system, pancreas, breast and prostate (Boffetta et al, 2006;de Menezes et al, 2013). Others have demonstrated that the first metabolite (acetaldehyde) of alcohol is a local carcinogen in humans (Salaspuro, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol consumption is associated with not only multiple health problems including cancer but also many social problems such as drunken driving, child abuse, and domestic violence; it also leads to substantial social expense (WHO, 2009;Osaki et al, 2012;de Menezes et al, 2013;Yaegashi et al, 2014). Screening tests have been proposed to identify alcohol use disorders.…”
Section: Introductionmentioning
confidence: 99%